MICROBIAL DIVERSITY AND BIOGEOGRAPHY IN A SERPENTINITE-HOSTED ECOSYSTEM - Woodruff, Quinn (East Carolina University, 2010)
The goal of this project was to characterize the taxonomic and functional diversity and document biogeographic patterns of microbial communities in an ecosystem influenced by active serpentinization. Serpentinization is a geochemical process which  occurs when ultramafic rocks characteristic of the Earth's mantle undergo aqueous alteration to produce altered mineral compositions (referred to as serpentines). This reaction results in highly-reduced, high pH fluids enriched in hydrogen, methane, and  small organic acids, and depleted in dissolved carbonate. Serpentinization is common in environments such as slow-spreading mid-ocean ridges, where tectonic activity on the  seafloor results in exposure of ultramafic rocks, and in ophiolites (sites where oceanic crust has been displaced onto continental margins). Environments associated with pervasive serpentinization tend to be anaerobic and highly alkaline (pH 10-12) and  creates a range of unique niches for microbial colonization and diversification. While the process of serpentinization provides abundant fuels to support the growth of chemotrophic microorganisms, the highly alkaline, highly reducing environmental  conditions challenge the limits of microbial physiology.    This work focuses upon the analysis of microbial communities that inhabit diverse niches within the Tablelands Ophiolite Complex, a serpentinizing environment located within Gros Morne National Park in western Newfoundland, Canada. A key element of this research was to assess the overall diversity of prokaryotic populations in a terrestrial serpentinite-hosted ecosystem and to evaluate how this diversity varies in relation to habitat characteristics. These analyses provided insight into the range of microorganisms that are able to exist in these settings, and provide a basis to explore their physiological and metabolic adaptations. A widely used method to assess the taxonomic diversity of microbial communities is through the analyses of the 16S ribosomal RNA (16S rRNA) gene. The 16S rRNA gene is an ideal target because it is functionally constant, of a sufficiently length to permit detailed phylogenetic analyses, and distributed throughout all domains of life. In addition to an assessment of microbial taxonomic diversity, this project was also concerned with discerning the spatial distribution of microbial communities, and how these populations differ based on their proximity to the alkaline seeps created by serpentinization.   Finally, all of these genetic assays were conducted against a backdrop of contextual data including total microbial cell counts determined by epifluorescence microscopy, viable cell counts by dilution plating on high pH media, and geochemical data. Taken together, this information provided a thorough report of how the abundance and the composition of microbial communities vary in relation to point sources of alkaline seepage.    Fluid and rock samples were collected in July 2009 and used to complete the analyses described above. Microscopic analyses found relatively low total cell concentrations (< 105 cells ml-1) with no discernable differences between sites. Phylogenetic analyses of bacterial 16S rRNA showed overall taxonomic diversity within the site ranging from Alpha Proteobacteria to Firmicutes. However, site to site diversity varied significantly, with minimal species overlap between communities.    This study represents one of the first detailed microbiological studies of a terrestrial serpentinite ecosystem. Furthermore, by mapping the diversity and abundance of organisms in relation to the point sources of seep fluids, we have begun to generate an idea of which organisms are serpentinite-influenced, and which are serpentinite-adapted, which will aid in the exploration of the serpentinite hosted biosphere.    Analysis of these samples indicated low diversity and low abundances compared to more moderate ecosystems, likely due to the challenges of living in highly basic environments such as maintaining membrane integrity and preventing cell lysis, generating a proton motive force across the cell membrane, and limited availability of exogenous terminal electron acceptors. In terms of diversity and species present, distinct patterns emerged concerning the spatial arrangement of microbial communities in relation to active serpentinization sites. Communities directly exposed to active alkaline seepage were subjected to high pHs and highly reducing conditions and were more limited in diversity, compared to more moderate sites. Overall, microbial diversity appeared to increase away from the point sources of alkaline seepage. This indicates that the taxonomic diversity and abundance of microbes is inversely affected by the alkaline, reduced conditions associated with serpentinization. The data supports a trend that in general, the more extreme the pH, the lower the microbial diversity. The range of species identified and diversity levels are similar to findings from other microbiological assessments of serpentinite ecosystems. Low diversity and species of Firmicutes and Alpha-proteobacteria have also been reported at sites such as a non-saline alkaline spring in Portugal and a slow-spreading mid-ocean ridge in the deep sea known as the Lost City Hydrothermal Field. The parallels between these sites suggest that serpentinization supports growth and activity of a narrow range of species, and that the extreme conditions associated with serpentinization will consistently limit microbial diversity.
Keywords: Biology, Microbiology; Microbiology; Environmental geochemistry--Newfoundland and Labrador; Geochemical surveys--Newfoundland and Labrador; Microbial ecology--Newfoundland and Labrador; Microorganisms--Evolution--Newfoundland and Labrador; Microbial growth--Newfoundland and Labrador; Gros Morne National Park (N.L.)